2014
DOI: 10.1038/bmt.2014.140
|View full text |Cite
|
Sign up to set email alerts
|

Palifermin reduces infection rate and hyperfibrinogenemia in patients treated with high-dose chemotherapy based on beam or BU-thiothepa

Abstract: We performed a retrospective study in patients who underwent high-dose chemotherapy and auto-SCT because of haematological malignancies. Forty patients were treated with palifermin while 80 were controls selected after being matched for diagnosis and length of neutropenia. Patients treated with BEAM or BU-CY or THIO-CY (BEAM/BUS) displayed, after palifermin, a lower rate of severe oral mucositis (P = 0.03). This beneficial effect of palifermin was not evident in the stratum of patients treated with high-dose m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…45 Another retrospective study reported that in patients undergoing BEAM (carmustine, etoposide, cytarabine and melphalan) or busulfan-thiotepa conditioned autologous HCT, treatment with palifermin is associated with a lower risk of febrile neutropenia and severe infections not related to gram-positive organisms. 46 Similarly, oral or intravenous glutamine can reduce the severity of mucositis, but clinical evidence for its efficacy in preventing infections is lacking. 47,48 Without any specific interventions, mucosal damage starts to heal just before, or with the recovery of granulocytes in peripheral blood (PB), 49 as neutrophil recruitment to the site of mucosal injury may occur up to a week before recovery of neutrophils in PB.…”
Section: Recovery Of Mucosal Injurymentioning
confidence: 99%
“…45 Another retrospective study reported that in patients undergoing BEAM (carmustine, etoposide, cytarabine and melphalan) or busulfan-thiotepa conditioned autologous HCT, treatment with palifermin is associated with a lower risk of febrile neutropenia and severe infections not related to gram-positive organisms. 46 Similarly, oral or intravenous glutamine can reduce the severity of mucositis, but clinical evidence for its efficacy in preventing infections is lacking. 47,48 Without any specific interventions, mucosal damage starts to heal just before, or with the recovery of granulocytes in peripheral blood (PB), 49 as neutrophil recruitment to the site of mucosal injury may occur up to a week before recovery of neutrophils in PB.…”
Section: Recovery Of Mucosal Injurymentioning
confidence: 99%
“…63 Other studies, however, found a positive impact of palifermin on infection rate after BEAM-like conditionings or after TBI. [64][65][66] Furthermore, some studies suggested that, though palifermin was not effective in reducing overall infection rate (mostly central venous catheter related), its use may reduce 'severe' infections such as those due to Gramnegative pathogens or accompanied by focal pneumonia. 66,67 In many centers, G-CSF administration is not routinely performed when the source of hematopoietic cells is mobilized peripheral blood, and the dose of CD34+ cells infused is largely above the threshold required for a proper engraftment.…”
Section: Hdc Administration Hpc Infusionmentioning
confidence: 99%